Hypoxia Contributes to Poor Prognosis in Primary IDH-wt GBM by Inducing Tumor Cells MES-Like Transformation Trend and Inhibiting Immune Cells Activity - Xiong, Zujian; Liu, Hongwei; He, Chenqi; Li, Xuejun (Frontiers in Oncology, 2021)
Aims To reveal the influence of hypoxia on tumor cells and immune cells in primary IDH-wt glioblastoma patients. Methods Single-cell RNA-seq data and bulk RNA-seq data were acquired from the GEO database and TCGA database respectively. Hypoxia status and subtypes of tumor cells were identified based on ssGSEA. Regulon network analysis of different subtypes under different conditions was conducted by SCENIC. Within tumor microenvironment, biological process activity analysis and cell-cell communication network were conducted to uncover the inner links between each cell subtype under different hypoxia status. Results Different types of tumor cell in GBM possessed different hypoxia status and MES-like subtype was under a more severe hypoxia condition than other subtypes. Hypoxia also induced MES-like signature gene expression within each tumor cell, which could stimulate tumor cell proliferation and invasion by regulating cell-cell communication. Additionally, hypoxia inhibited immune cell activity in the tumor microenvironment by inducing macrophage phenotype polarization and upregulating immune-inhibited cell-cell interaction within immune cells. Interactions between tumor cells and immune cells under hypoxia status also promoted tumor progression. Conclusions Hypoxia was a poor prognostic marker for primary IDH-wt GBM patients. Meanwhile, it could induce tumor cells MES-like transformation trend and inhibit anti-tumor function of immune cells.